EFEK SUHU DAN LAMA PEMANASAN TERHADAP SIFAT FISIKA-KIMIA BUBUK PEWARNA DARI KELOPAK BUNGA ROSELA (Hibiscuss sabdariffa L.) YANG DIHASILKAN - Yuliani - (PROSIDING SEMINAR KIMIA, 2013)
Roselle (Hibiscus sabdariffa L.) calyces can be used as natural food colorant. The objective of this study is to observe the effect of drying time and temperature on physical and chemical characteristic of rosela calyces powder. The experiment is arranged in Completely Randomized Design and each treatment is replicated by three times. The factors are drying temperature (60, 70, 80 C) and drying time (5, 7, 9 h). The results showed that the combined treatment of drying temperature at 80 C and drying time for 5 h gave the best result, i.e yield of 9.46 %, water absorption of 1.92 g/g sampel, color intensity of 1 % rosella calyces powder solution showed an absorbance of 0.28 at 605 nm, water content 6.42 %, ash content 0.51 %, and total acid of 5.14 % as malic acid.